Do parasite infections interfere with immunisation? A review and meta-analysis. Issue 35 (31st July 2020) - Wait, Liana F.; Dobson, Andrew P.; Graham, Andrea L.
Abstract: Immune responses to vaccination are heterogeneous between individuals; the same vaccine that provides protection in one circumstance may be ineffective in another. One factor that could influence the response to vaccination is concurrent or prior infection with unrelated parasites. Here, we review both the experimental and epidemiological literature on parasite-vaccine interactions, and present a meta-analysis of the published data. In total, our review returned 101 relevant articles, 50 of which met criteria for meta-analysis. Parasite factors potentially affecting vaccination include the type of parasite involved, the stage of infection, and the timing of infection relative to vaccination. Vaccine factors affecting likelihood of interference by parasites include vaccine formulation, route of administration, and the type of immune response required to provide protection against the target antigen. Our meta-analysis of these data show three key things: (1) parasite infections at the time of vaccination result in worse immunisation outcomes, (2) chronic helminth infections are more likely to negatively impact immunisation than acute helminth infections, and (3) thymus-dependent vaccines are more susceptible to parasite interference than thymus-independent vaccines. Our findings highlight the importance of considering and mitigating parasite infections: by taking parasites into account, it should be possible to more effectively immunise individuals and populations.